2018
DOI: 10.1155/2018/9541459
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Abrogates Matrix Metalloproteinase-9 Expression by Inhibition of NF-κB Activation in Stimulated Human Monocytic Cells

Abstract: Much evidence has indicated that matrix metalloproteinases (MMPs) participate in the progression of neuroinflammatory disorders. The present study was undertaken to investigate the inhibitory effect and mechanism of the antipsychotic haloperidol on MMP activation in the stimulated THP-1 monocytic cells. Haloperidol exerted a strong inhibition on tumor necrosis factor- (TNF-) α-induced MMP-9 gelatinolysis of THP-1 cells. A concentration-dependent inhibitory effect of haloperidol was observed in TNF-α-induced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…C57BL/6 mice were processed for intrastriatal LPS injection as previously described [57]. LPS was dissolved in sterilized normal saline and 3 μL (equivalent to 4 μg LPS) was injected.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were processed for intrastriatal LPS injection as previously described [57]. LPS was dissolved in sterilized normal saline and 3 μL (equivalent to 4 μg LPS) was injected.…”
Section: Methodsmentioning
confidence: 99%
“…Metalloproteinases play an important role in schizophrenia and other neuropsychiatric disorders probable by abnormal synaptic plasticity and functional reorganization of excitatory synapses that are located on dendritic spines [ 41 ]. Moreover, metalloproteinases influence learning and memory processes and are linked to progression of neuroinflammatory disorders [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the scarcity of data concerning the studied issue, it is worth noting that pharmacotherapy of neurodegenerative diseases of the central nervous system (typical neuroleptics medication, memantine) also has an impact on the expression of metalloproteinase genes and their inhibitors. A correlation has been found between the dose of haloperidol and expression of mRNA MMP-9 and TIMP-1, with no effect on MMP-2 within the range of monocytes [45]. It has been observed that the MMP-9 polymorphism and severity of traumatic events in childhood have an effect on the response to flupentixol treatment in the population of patients with the first episode of schizophrenia [46].…”
Section: Discussionmentioning
confidence: 99%